Hubungan Dermatofitosis dengan Diabetes Melitus Tipe 2 di RSUD Sanjiwani Gianyar - Ni Wayan Winiati; Sayu Widiawati; Ni Made Tirta Ningsih (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2022)
Dermatophytosis is a disease that affects tissues containing horny substances, such as the stratum corneum of the epidermis, hair and nails caused by dermatophyte fungi. Theoretically, it is stated that one of the predisposing factors for dermatophytosis is Diabetes Mellitus (DM). High blood glucose levels in diabetics causes an increase in skin glucose which can interfere with the immune process and supply energy for the fungus to develop, so that it is easy for manifestations of skin disorders to appear, one of which is dermatophytosis. The purpose of this study was to determine the relationship between dermatophytosis and Type 2 DM at the Sanjiwani Hospital, Gianyar. The method used in this study is analytical observation using a case control approach in the Medical Record section of the Sanjiwani Hospital, Gianyar. The minimum sample of this study amounted to 150 people who were divided into two groups. The case group consisted of 75 people and the control group consisted of 75 people who met the inclusion and exclusion criteria. The Odd Ratio value of this study was 3.63 (95% CI 1.35 - 9.76). The results showed that there was a relationship between dermatophytosis and Type 2 DM. Patients with Type 2 DM had a 3.63 times higher risk of suffering from dematophytosis than people without Type 2 DM (p = 0.008 (p<0.05)).